Scivolando verso il basso. L’inserimento lavorativo dei nuovi migranti italiani e spagnoli in Germania durante la crisi economica - Castellani, S. (Sociologia del Lavoro, 2018)
During the last years, the freedom of movement in the EU has represented a chance for the workers of Peripheral-countries, affected by the economic crisis, to find employment opportunities in the Core-countries. However, right in these countries the requests to limit EU citizens’ mobility and welfare access are becoming stronger. Drawing from an ethnographic study carried out in two German regions with Italians and Spaniards aged 18-39 years who moved to Germany for work since 2008, the paper first, analyses the systemic dynamics which conditions the intra-UE contemporary mobility. Secondly, it highlights how the majority of Italians and Spaniards enter the secondary German labour market, even if they have a cosmopolitan profile, shaping a differential inclusion in the host society.